PENGEMBANGAN MEDIA MONOPOLI “GEMAS” DALAM MENINGKATKAN PENGETAHUAN PESAN UMUM GIZI SEIMBANG PADA SISWA SD KELAS IV (Jurnal Kesehatan Siliwangi, 2021)
Indonesia is currently facing a double nutrition problem. There are two types of malnutrition: undernutrition and overnutrition. Socialization activities of balanced nutrition guidelines are required to prevent the nutritional problems. Education through learning media in the form of educational games is one kind of health education that can be used. Monopoly games are a fun and instructive way to provide information. Referring to the problem, the research “Development of Monopoly Media "Gemas" as an Alternative Media in Improving Knowledge of General Message Balanced Nutrition in Elementary School Students Grade IV” is conducted. The focus of this research is to develop the "GEMAS" monopoly media and compare the value of general message balanced nutrition before and after the monopoly game in grade IV students from West Bandung Regency. To assess student knowledge progress, this research used the P Process technique as well as a One-Group Pretest-Posttest design model without control group. The subjects of the research are 15 students of grade IV. According to the findings, the monopoly media "GEMAS" is "Very Decent," with an overall value of 90.5 %. There is also a difference in the average value of knowledge before and after playing monopoly, which ranges from 50.6 to 75.07. Paired-sample t-test results obtain a Sig value. (2-tailed) of 0.000 < 0.005 or H0 is rejected and H1 is accepted. As a result, it can be concluded that the monopoly game "GEMAS" is worth to use, and it can help grade IV students at West Bandung Regency understand the importance of general message of balanced nutrition.